A novel luminescence‐based method for the detection of functionally active antibodies to muscarinic acetylcholine receptors of the M3 type (mAchR3) in patients' sera. (July 2014) - Preuss, B.; Tunaru, S.; Henes, J.; Offermanns, S.; Klein, R.
Summary In different bioassays, functional antibodies reacting with the human muscarinic acetylcholine receptor M3(mAchR3) have been detected in sera from patients with Sjögren's syndrome (SS), and there is strong evidence that those antibodies may have pathogenetic relevance. However, depending on the method of detection, their prevalence varied. Furthermore, those bioassays are difficult to standardize. We report on the development and optimization of a novel test system based on a luminometric method to determine downstream signalling of mAchR3 which produces specific and reproducible results. Chinese hamster ovarian (CHO) cells were transfected with plasmids encoding mAchR3 and a green fluorescence protein (GFP)/aequorin fusion protein. Incubation of cells with carbachol resulted in an increase in intracellular [Ca2+], which was detected by measuring light emission with a luminometer, and the effect of incubation with patients' immunoglobulins (Ig) was evaluated. Optimal cell density, Ig preparation and time of incubation with patients' sera were determined. Sera from patients with primary Sjögren's syndrome (pSS; n = 40), systemic sclerosis (SSc; n = 47), myasthenia gravis (MG; n = 133) and 50 blood donors were analysed. Optimal assay conditions were obtained with a cell density of 100 000 cells/ml, isolation of Ig by ammonium sulphate precipitation and short‐term incubation. Based on this highly reliable assay, 50% of the pSS patients had antibodies which inhibited carbachol‐induced activation of mAchR3; none of the SSc patients, 6% of the patients with MG and 12% of the blood donors had antibodies which reacted with the mAchR3. This method facilitates the determination of functional anti‐mAchR3 antibodies in patients' sera, confirmed their high prevalence in pSS patients and may, therefore, help to analyse their pathogenetic and clinical relevance in more detail.